Polar Quasinormal Modes of Neutron Stars in Massive Scalar-Tensor Theories - Blázquez-Salcedo , Jose Luis; Khoo , Fech Scen; Kunz , Jutta; Preut , Vincent (Frontiers in Physics, 2021)
We study polar quasinormal modes of relativistic stars in scalar-tensor theories, where we include a massive gravitational scalar field and employ the standard Brans-Dicke coupling function. For the potential of the scalar field we consider a simple mass term as well as a potential associated with R2 gravity. The presence of the scalar field makes the spectrum of quasinormal modes much richer than the spectrum in General Relativity. We here investigate radial modes (l = 0) and quadrupole modes (l = 2). The general relativistic l = 0 normal modes turn into quasinormal modes in scalar-tensor theories, that are able to propagate outside of the stars. In addition to the pressure-led modes new scalar-led ϕ-modes arise. We analyze the dependence of the quasinormal mode frequencies and decay times on the scalar field mass.